2002
DOI: 10.1071/ar02041
|View full text |Cite
|
Sign up to set email alerts
|

Production of zearalenone, deoxynivalenol, nivalenol, and acetylated derivatives by Australian isolates of Fusarium graminearum and F.pseudograminearum in relation to source and culturing conditions

Abstract: Australian isolates of Fusarium pseudograminearum (Fp = F. graminearum Group 1) and F. graminearum (Fg = F. graminearum Group 2) can produce mycotoxins including zearalenone (ZEA), 4-deoxynivalenol (DON), and nivalenol (NIV). Fp isolates from wheat and barley tillers in southern Queensland all produced ZEA and DON in culture, and one typical isolate also produced 3-acetyldeoxynivalenol. Most Fg isolates from wheat and sorghum grains in southern Queensland produced ZEA and DON and one typical isolate also produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…Several researchers (18,19,38) have reported that isolates with the 3-ADON marker are dominant in warm regions and that isolates with the 15-ADON marker are found mainly in cool regions. The occurrence of different trichothecene-producing isolates of G. zeae reported here and in previous studies (2,7,18,22,34) may be due to the relatively wide range of environmental conditions under which the host crops are grown. In particular, temperature and precipitation (11,14) and substrate composition (31) were reported previously to be major factors influencing trichothecene production by G. zeae.…”
Section: Vol 74 2008 Mycotoxin Production By Gibberella Zeae 6517mentioning
confidence: 81%
See 1 more Smart Citation
“…Several researchers (18,19,38) have reported that isolates with the 3-ADON marker are dominant in warm regions and that isolates with the 15-ADON marker are found mainly in cool regions. The occurrence of different trichothecene-producing isolates of G. zeae reported here and in previous studies (2,7,18,22,34) may be due to the relatively wide range of environmental conditions under which the host crops are grown. In particular, temperature and precipitation (11,14) and substrate composition (31) were reported previously to be major factors influencing trichothecene production by G. zeae.…”
Section: Vol 74 2008 Mycotoxin Production By Gibberella Zeae 6517mentioning
confidence: 81%
“…TRI3-and TRI12-based multiplex PCR assays were used to differentiate between G. zeae isolates associated with the 3-ADON marker and the 15-ADON marker. 2 analysis revealed a highly significant difference ( 2 ϭ 22.52; P Ͻ 0.0001) in the frequencies of genetic markers for 3-ADON and 15-ADON in G. zeae isolates from four crops. …”
Section: Chemical Analysis Of Mycotoxins By Gc-msmentioning
confidence: 99%
“…ZON has several derivatives, such as ␣-zearalenol, that have greater estrogenic activity than ZON (47). ZON is produced by several Fusarium species, including F. graminearum, F. culmorum, F. cerealis (synonym, F. crookwellense), F. equiseti, F. semitectum (53), and F. pseudograminearum (5). There have also been reports of ZON production by other Fusarium species, but their accuracy has been questioned (53), as Fusarium taxonomy is complex and chemical analyses are not always clear-cut (29,51).…”
mentioning
confidence: 99%
“…As explained above, this fungus is only common in Australia on the cool, wet tablelands of Far North Qld, where for reasons not completely clear, the fungus produces mainly NIV. In southern Qld and in NSW, the fungus produces mainly DON, also called vomitoxin (Blaney and Dodman 2002). It is very unusual for NIV and DON to exceed 1 mg/kg, a level reducing feed intake by pigs (Williams and Blaney 1994).…”
Section: Nivalenol and Deoxynivalenolmentioning
confidence: 99%
“…Tricothecenes known to contaminate maize include DON, also referred to as vomitoxin, and NIV (Blaney & Dodman 2002;Blaney, Moore & Tyler 1984;CAST 2003;JECFA 2012). The chemical structures of these toxins are illustrated in Figures 2-8 and 2-9.…”
Section: Tricothecenesmentioning
confidence: 99%